GILLS VISUALIZATION OF TILAPIA AND MORTALITY RATES USING THE LETHAL 50 METHOD TO DETECT SUBLETHAL OIL POLLUTION IN RIVER WATER BODIES - Alifah Mutiara Susanto; Achmad Fudianto; Anastasya Nabila Cornelius; Zelbia Redina Siwi Budi M; Ajeng Daniarsih (Universitas Medan Area, 2026)
Environmental issues in Indonesia are mostly caused from pollution resulting from industry and domestic waste. Oil and used cooking oil are examples of waste that are often produced from both. Water contaminated by these chemicals can affect organisms living in it, one of which is tilapia (Oreochromis niloticus). Hazardous chemicals can accumulate in tilapia through the food chain, absorption through the gills, or diffusion through the skin surface, potentially causing death. This study aims to determine the effect of used cooking oil and motor oil waste on gill morphology and mortality of tilapia. The study was conducted for 96 hours using an experimental method by testing the effect of used cooking oil and used oil with concentrations of 1%, 3%, 5% on tilapia (O. niloticus). The parameters observed in the study were gill morphology and calculating the number of fish mortalities. The results show that increased concentrations of used cooking oil and motor oil increased tilapia mortality, with the highest mortality at a concentration of 5%, indicating that exposure had exceeded the sublethal threshold and was lethal.